Violence & society - Ray, Larry J.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2011)
In this compelling work, Larry Ray offers a wide-ranging and integrated account of the many manifestations of violence in society. He examines violent behaviour and its meanings in contemporary culture and throughout history.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Violence; Electronic books